Polymeric based nanoparticles carrier for improved antibiotic delivery. - Lin, Ivy Siew Leng. (2013)
In the advance of medical knowledge and technologies, infectious diseases continue to be one of the major challenges faced in the healthcare system. The rapid mutation of microorganism causing antibiotic resistant and the difficulty of antibiotic delivery to poorly vascularised sites prevented and compromised the treatment of chronic infections using conventional systemic antibiotic therapy. As a result, this called for an alternative method to improve the antibiotic drug performance.